CBFβ and the Leukemogenic Fusion Protein CBFβ‐SMMHC Associate With Mitotic Chromosomes to Epigenetically Regulate Ribosomal Genes. Issue 12 (15th October 2014) - Lopez‐Camacho, Cesar; van Wijnen, Andre J.; Lian, Jane B.; Stein, Janet L.; Stein, Gary S.
ABSTRACT Mitotic bookmarking is an epigenetic control mechanism that sustains gene expression in progeny cells; it is often found in genes related to the maintenance of cellular phenotype and growth control. RUNX transcription factors regulate a broad spectrum of RNA Polymerase (Pol II) transcribed genes important for lineage commitment but also regulate RNA Polymerase I (Pol I) driven ribosomal gene expression, thus coordinating control of cellular identity and proliferation. In this study, using fluorescence microscopy and biochemical approaches we show that the principal RUNX co‐factor, CBFβ, associates with nucleolar organizing regions (NORs) during mitosis to negatively regulate RUNX‐dependent ribosomal gene expression. Of clinical relevance, we establish for the first time that the leukemogenic fusion protein CBFβ‐SMMHC (smooth muscle myosin heavy chain) also associates with ribosomal genes in interphase chromatin and mitotic chromosomes to promote and epigenetically sustain regulation of ribosomal genes through RUNX factor interactions. Our results demonstrate that CBFβ contributes to the transcriptional regulation of ribosomal gene expression and provide further understanding of the epigenetic role of CBFβ‐SMMHC in proliferation and maintenance of the leukemic phenotype. J. Cell. Biochem. 115: 2155–2164, 2014. © 2014 Wiley Periodicals, Inc.